Economic Status and Maternal Health: Analysis of the 2013-14 Zambia Demographic and Health Survey - Mulenga, Mulenga Chonzi (Open Science Journal, 2017)
With the current high maternal mortality rates prevailing in Zambia, it is imperative to analyze the effect that the economic status of women has on maternal health outcomes. It is hypothesized that wealth is positively linked to better health outcomes. As a result, maternal health outcomes will improve when the economic status of women improve. Using data for women from the 2013-14 Zambia Demographic and Health Survey, bivariate and multivariate analysis was used to ascertain the impact of wealth as a proxy for economic status and other variables based on five independent outcomes (Number of antenatal care visits, timing of first antenatal care visit, tetanus toxoid vaccination, iron tablet/syrup uptake, and place of delivery) and a composite measure of maternal health. The results revealed that women’s wealth and region were the only significant factor associated with all the five independent indicators and the composite measure of maternal health. However, for the composite measure, literacy and age of the mother were also found to be associated with maternal health. The study therefore concluded that economic status is an important factor in improving maternal health outcomes in Zambia. As a result, policy should be aimed at providing support to women within the lowest wealth quintiles so as to enable them access maternal health services.